Analisis Penerapan Karakter Jujur Perspektif Thomas Lickona Melalui Program PIN Kejujuran Siswa SDN Purwoyoso 03 - Rokhim, An Najmun Nuri; Abidah, Wulan Nur; Az Zahra, Hayya Fathimah; Zainiyah, Yiyin Syifa; Kiptiyah, Siti Maryatul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The urgency of honest character education is increasingly pressing amidst the decline in moral values, so there is a need for innovation in the implementation of character education. This article analyzes the application of honest character to students at SDN Purwoyoso 03 through the application of the Honesty Pin from Thomas Lickona's perspective as a form of innovation in overcoming the urgency of character education. Thomas Lickona emphasized that honesty is the main pillar in character education which must be instilled from an early age. The Honesty Pin Program at SDN Purwoyoso 03 aims to internalize the value of honesty in students' daily lives. This research applies qualitative methods through interviews, observation, data reduction, and triangulation of point recording data. The results of the analysis show that the application of the Honesty Pin is effective and has a positive influence in implementing students' honest character, creating a school environment with integrity, and inspiring consistent honest behavior. However, besides this, the implementation of the Honesty Pin has obstacles, namely teacher and student factors. This article is expected to provide in-depth insight into the implementation of honest character education and suggest the development of similar programs for other schools to improve the overall quality of character education.The urgency of honest character education is increasingly pressing amidst the decline in moral values, so there is a need for innovation in the implementation of character education. This article analyzes the application of honest character to students at SDN Purwoyoso 03 through the application of the Honesty Pin from Thomas Lickona's perspective as a form of innovation in overcoming the urgency of character education. Thomas Lickona emphasized that honesty is the main pillar in character education which must be instilled from an early age. The Honesty Pin Program at SDN Purwoyoso 03 aims to internalize the value of honesty in students' daily lives. This research applies qualitative methods through interviews, observation, data reduction, and triangulation of point recording data. The results of the analysis show that the application of the Honesty Pin is effective and has a positive influence in implementing students' honest character, creating a school environment with integrity, and inspiring consistent honest behavior. However, besides this, the implementation of the Honesty Pin has obstacles, namely teacher and student factors. This article is expected to provide in-depth insight into the implementation of honest character education and suggest the development of similar programs for other schools to improve the overall quality of character education.Keywords: Honesty, Character, Thomas Lickona, Honesty Pin Article Info